2015
DOI: 10.1021/acs.cgd.5b00125
|View full text |Cite
|
Sign up to set email alerts
|

Extenuation of Stress and Defects in GaN Films Grown on a Metal–Organic Chemical Vapor Deposition-GaN/c-Sapphire Substrate by Plasma-Assisted Molecular Beam Epitaxy

Abstract: We investigated curbing the defects and stress/strain in epitaxially grown crystalline GaN films on a metal−organic chemical vapor deposition-GaN/c-sapphire (MGcS) template by using plasma-assisted molecular beam epitaxy and demonstrated the impact of growth temperature on their structural, morphological, and optical properties. An in-plane compressive stress having a minimum value of 0.34 GPa has been investigated by vibrational spectroscopy. This alleviated stress was attributed to a less pitted and smoother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 39 publications
4
26
1
Order By: Relevance
“…lattice constant estimation using Bragg's law. [18] The calculated value of strain in the grown structure is realized to be 0.25% which confirms strain relaxation in the grown nanotowers. Further, to analyse the dislocation density, HRXRD omega scans along (0002) and (10-12) plane of diffraction have been performed as shown in figure 2(a).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…lattice constant estimation using Bragg's law. [18] The calculated value of strain in the grown structure is realized to be 0.25% which confirms strain relaxation in the grown nanotowers. Further, to analyse the dislocation density, HRXRD omega scans along (0002) and (10-12) plane of diffraction have been performed as shown in figure 2(a).…”
Section: Resultssupporting
confidence: 54%
“…[21] The observed red-shift in the E2 (high) position specifies of tensile stress in the grown GaN-NTs. [25,26] The value of tensile stress [18] is estimated to be 0.092 GPa which is significantly lower as compared to 3D GaN-NSs and 2D GaN films [27][28][29] which can be attributed to lower defect states. Further, it has been proposed that these defects can have an adverse impact on electrical as well as the optical property of the GaN-based UV PD.…”
Section: Resultsmentioning
confidence: 99%
“…The ex-situ wet chemical cleaning of the substrates was performed via standard cleaning procedure [18]. The GaN films (thickness varied from 0.8 to 1.1 mm) were grown at a constant substrate temperature of 735 C with plasma power varying from 350 W to 500 W, keeping all other parameters as constant.…”
Section: Methodsmentioning
confidence: 99%
“…Tsai et al also reported that edge dislocations are dominant in Ga-stable growth regime [19]. The obtained screw and edge dislocation densities were further integrated to evaluate the total threading dislocation density (TDD) in the grown GaN films [18]. Hence, via using the FWHM values measured from RC of grown samples, the TDD was calculated to be 2.65 Â 10 7 cm À2 , 2.62 Â 10 7 cm À2 and 2.4 Â 10 7 cm À2 for S1, S2 and S3 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…5b) shows slightly smooth surface morphology (r.m.s. roughness, R r.m.s = 6.44 nm) covered with small troughs which were assumed to be appeared due to the nitrogen vacancies in epitaxial AlN buffer layer that was grown in Al-rich conditions [27]. As the buffer growth temperature increases to 780 °C (Fig.…”
Section: Morphological Propertiesmentioning
confidence: 99%